Lighter and Simpler Design Paradigm for Widespread Use of Ankle Exosuits Based on Bio-Inspired Patterns - Sungjin Park; Junyoung Moon; June il Park; Jaewook Ryu; Kimoon Nam; Jaeha Yang; Giuk Lee (Biomimetics, 2022)
Soft wearable robots are attracting immense attention owing to their high usability and wearability. In particular, studies on soft exosuits have achieved remarkable progress. Walking is one of the most basic human actions in daily life. During walking, the ankle joint has considerable influence. Therefore, an exosuit design paradigm having a light and simple structure was developed with the goal of fabricating a soft exosuit that supports the ankle. The new exosuit matches the performance of existing exosuits while being as comfortable as everyday wear. A walking test through a combination with a mobile actuator system, which can maximize these advantages, was also conducted. The combination with the mobile system demonstrates the potential of using the new ankle exosuit as inner wear that maximizes the advantages of a lighter and simpler design. The exosuit design paradigm could serve as an effective guideline for manufacturing assistive exosuits for various body parts in the future.